Monitoring and Assessment of Environmental Quality in Coastal Ecosystems (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Coastal ecosystems are dynamic, complex, and often fragile transition environments between land and oceans. They are exclusive habitats for a broad range of living organisms, functioning as havens for biodiversity and providing several important ecological services that link terrestrial, freshwater, and marine environments. Humans living in coastal zones have been strongly dependent on these ecosystems as a source of food, physical protection against storms and advancing sea, and a range of human activities that generate economic income. Notwithstanding, the intensification of human activities in coastal areas of the recent decades, as well as the global climatic changes and coastal erosion processes of the present, have had detrimental impacts on these environments. Maintaining the structural and functional integrity of these environments and recovering an ecological balance or mitigating disturbances in systems under the influence of such stressors are complex tasks, only possible through the implementation of monitoring programs and by assessing their environmental quality. In this book, distinct approaches to environmental quality monitoring and assessment of coastal environments are presented, focused on abiotic and biotic compartments, and using tools that range from ecological levels of organization to the sub-organismal and the ecosystem levels.